Memórias e história de vida de uma professora: da infância à docência - LOUREIRO, Priscila Martins (2019)
This work is a memorial, dealing with the memories and life history of a teacher, woven by difficulties, overcoming in a past and present time. The objective outlined between the narratives was to give meaning to events and life experiences, seeking to interpret the practices that contributed to the formation. This investigation took life history as a methodological possibility, accompanied by the semi-structure interview. The theoretical references were Nóvoa (1989) (2017), Bragança (2012), Louro (1997), Candau Candau (2012), among others. Writing allowed me to document descriptively and reflexively the memories and facts that made sense in my life, a sort of selection of experiences and events that marked my life story, constituting me as a teacher. This movement of reading, writing and research became a rewarding challenge, as I had to remember my past by bringing up events that were stored in my memory in the forgetfulness zone. Finally, I relived fragments of memories of my childhood, the process of schooling and teaching, smiling, I was moved, and today I have the conviction that I am in the right profession.